2020
DOI: 10.31234/osf.io/95ujm
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sleep quality, timing, and psychological difficulties in Italian school-age children and their mothers during COVID-19 lockdown

Abstract: Background. By March 10th, 2020, the Italian Government has ordered a national lockdown to limit viral transmission of COVID-19 infection, which establishes home confinement, movement restriction, home (smart) working, and temporary closure of non-essential businesses and schools of every order and degree. The current study investigated how these restrictive measures impacted sleep quality, timing, and psychological difficulties in school-age children and their mothers during the lockdown.Methods. Using an onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 28 publications
1
12
0
1
Order By: Relevance
“…43 Our findings are among the first to provide objective data that support retrospective parental perceptions of decreased activity and increased sedentary behaviour among pre-adolescents (age 8-12), 9 and are among the first conducted in the United States. worrisome, [14][15][16] as sleep timing, independent of sleep duration, is linked with overweight and obesity. 43 Evidence for potential health impacts of changes in children's health behaviours stems from previous work examining behavioural changes during extended breaks from the structured school year (e.g., summer vacation), weekends and short breaks (e.g., spring/winter break).…”
Section: Resultsmentioning
confidence: 99%
“…43 Our findings are among the first to provide objective data that support retrospective parental perceptions of decreased activity and increased sedentary behaviour among pre-adolescents (age 8-12), 9 and are among the first conducted in the United States. worrisome, [14][15][16] as sleep timing, independent of sleep duration, is linked with overweight and obesity. 43 Evidence for potential health impacts of changes in children's health behaviours stems from previous work examining behavioural changes during extended breaks from the structured school year (e.g., summer vacation), weekends and short breaks (e.g., spring/winter break).…”
Section: Resultsmentioning
confidence: 99%
“…Research conducted during the lockdown on parents with children aged 6–10 years showed that the wake-up- and bedtimes were delayed for both mothers and children. Further, the quality of sleep for both the parents and children declined; the “boredom” and “psychological difficulty of the mother” also increased [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the imposed restrictions have negatively affected several life domains among young people, although the direct health impact of COVID-19 seems lower in this population than among older adults. Youths reported reduced health-related quality of life [ 4 ], negative psychological and emotional outcomes [ 5 , 6 , 7 ], behavioral difficulties such as sleeping problems [ 8 ], poor nutritional regimen [ 9 ], increased sedentariness and screen-time [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%